(untitled) (Biological Sciences - PJSIR, 1995)
Trace elements Ag, Au, Ca, Cl (Ca and Cl were estimated titrimetrically by EDTA and Cl by ion selective electrode), Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, Sr and Zn in barley, beet and purslane (leaves, stems, tubers and grains) as well as in the soil samples taken from the immediate vicinity of plant roots (10, 30 and 60 em depths) in Klabsha area, an experimental farm of the High Dam Lake Development Authority, were estimated. The results show that purslane accumulates Ca, Cl, Fe, K, and Na, beet accumulates Au, Ca, Co, Cl, Mg, Mn and Na while Co, Cr, Cu and Zn are more concentrated in grains of barley than in its leaves (Ca, Cl, Fe, Mg, Mn, Na Sr and Ni are more concentrated in leaves than in grains).